Combining spatial filtering and wavelet transform for classifying human emotions using EEG Signals - Murugappan; Nagarajan, Ramachandran, Prof. Dr.; Sazali, Yaacob, Prof. Dr. (Biomedical Engineering Society of the R.O.C., 2011)
Link to publisher's homepage at http://www.bmes.org.tw/